92 x (x+1)-3=23+(72x 2) : 14
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2:
1: =>36x+14x=69+81=150
=>50x=150
=>x=3
2: 3^x=81
=>3^x=3^4
=>x=4
3: 3(2x+1)^2=75
=>(2x+1)^2=25
=>2x+1=5 hoặc 2x+1=-5
=>x=-3 hoặc x=2
1:
1: \(\dfrac{13\cdot17^4+4\cdot17^4}{17^3}-\dfrac{14\cdot3^3-14\cdot3^2}{9}\)
\(=\dfrac{17^4\cdot\left(13+4\right)}{17^3}-\dfrac{14\cdot3^2\left(3-1\right)}{9}\)
\(=17\cdot17-14\cdot2\)
=289-28
=261
2:
\(2^3\cdot5^2-\left[131-\left(23-2^3\right)^2\right]\)
\(=8\cdot25-131+\left(-1\right)^2\)
=69+1
=70
X + 8 = 22
X = 22 − 8
X = 14
X + 14 = 92
X = 92 − 14
X = 78
23 + x = 62
X = 62 − 23
X = 39
(5 - \(x\))(9\(x^2\) - 4) =0
\(\left[{}\begin{matrix}5-x=0\\9x^2-4=0\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=5\\9x^2=4\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=5\\x^2=\dfrac{4}{9}\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=5\\x=-\dfrac{2}{3}\\x=\dfrac{2}{3}\end{matrix}\right.\)
Vậy \(x\) \(\in\) { - \(\dfrac{2}{3}\); \(\dfrac{2}{3}\); \(5\)}
72\(x\) + 72\(x\) + 3 = 344
72\(x\) \(\times\) ( 1 + 73) = 344
72\(x\) \(\times\) (1 + 343) = 344
72\(x\) \(\times\) 344 = 344
72\(x\) = 344 : 344
72\(x\) = 1
72\(x\) = 70
\(2x\) = 0
\(x\) = 0
Kết luận: \(x\) = 0
mình giải ý c
5(x+27)=200
(x+27)=200:5
(x+27)=40
x=40-27
x=13
b) \(\left(x-1\right)^3=\dfrac{1}{8}\)
\(\left(x-1\right)^3=\left(\dfrac{1}{2}\right)^3\)
\(x-1=\dfrac{1}{2}\)
\(x=\dfrac{1}{2}+1\)
\(x=\dfrac{3}{2}\)
92.(x + 1) - 3 = 23 + (72.2) : 14
81.(x + 1) - 3 = 8 + 98 : 14
81.(x + 1) - 3 = 8 + 7
81.(x + 1) - 3 = 15
81.(x + 1) = 15 + 3
81.(x + 1) = 18
x + 1 = 18 : 81
x + 1 = 2/9
x = 2/9 - 1
x = -7/9